The Role of Fiqh of Balancing in Achieving Social Peace - Luqman Bahaaulddin Ahmed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
This study discusses the role of the Fiqh of Balancing, in achieving social peace. Social peace is one of the main purposes of human societies in general, and Islamic society in particular. In this regard, the Islamic Shareea has necessitated to achieve five goals which are the protection of religion, soul, mind, (nasl) Progeny, and wealth. Keeping these five necessities contribute in the achievement of social peace with all its dimensions, because it will fulfill the stability of the life of individuals and communities, and it will positively affect the well-being and develops all dimensions of life. Since the clashes of the interests and disadvantages threaten the achievement of social peace, the Fiqh of Balancing must be considered to keep the balance between the interests and disadvantages when they confront. The Fiqh of Balancing favors what shall be favored, delays what should be delayed and give adequate consideration and care to everything. This Fiqh is based on the Fiqh of Script and the Fiqh of Reality, with consideration to the Purposes of Shareea and the consequences of the actions.